Faith, Diversity, and Education: Measuring Islamic Worldview as a Driver of Multicultural Moderation - Ridha, Achmad Rasyid; Sukari, Sukari; Rokhimah, Siti; Ellwern, Kaspar; Keller, Jonas (Universitas Muhammadiyah Surakarta, 2026)
The increasing complexity of multicultural societies has intensified the need for educational frameworks capable of fostering religious moderation without weakening theological commitment. Within Islamic educational contexts, moderation is frequently discussed as a normative ideal; however, empirical and measurement-based approaches remain limited. The absence of validated instruments for assessing Islamic worldview and its relationship to multicultural moderation has constrained the development of evidence-based educational policies and institutional practices. This research aimed to examine the implementation of the Integrated Islamic School Moderation Framework through the measurement of Islamic worldview among educational personnel in Indonesia. A quantitative research design was employed using a cross-sectional survey approach involving 250 educational personnel from Integrated Islamic Schools affiliated with the Jaringan Sekolah Islam Terpadu (JSIT) Indonesia across 26 provinces. Data were collected using a situational judgment-based Islamic Worldview Scale and analyzed through Confirmatory Factor Analysis (CFA) using LISREL 8.8 to evaluate construct validity, reliability, and model fit. The findings revealed that Islamic moderation is empirically structured through two interconnected dimensions: commitment to ats-tsawābit (immutable religious principles) and accommodative engagement with al-mutaghayyirāt (dynamic sociocultural contexts). Both dimensions demonstrated acceptable goodness-of-fit indices and high construct reliability, indicating that strong theological commitment can coexist with multicultural openness and democratic engagement. The study further demonstrates that Islamic moderation can be operationalized as a measurable educational construct rather than merely a normative discourse. These findings contribute to the advancement of measurement-based Islamic education research and provide a conceptual and empirical foundation for developing moderation-oriented educational policies, teacher development programs, and multicultural learning environments within Islamic schools